EFL through Play and Art - Medrano Toapanta, Daysi Tatiana (2013)
The purpose of this proposal is to determine whether EFL through Play and Art” as an innovative EFL teaching philosophy improves the English language acquisition process among eight to ten-year olds. The EFL through Play and Art” is a teaching philosophy whose main concern is the development of a more real and natural foreign language acquisition process through the use of transformed textbook activities into games and art work in young children while acquiring English. A multiple case study research methodological design was selected to assess the validity and reliability of this innovative EFL teaching philosophy. This dissertation seeks to demonstrate that the use of games and art work enhance the acceptability of English as a foreign language among eight to ten –year olds. In the end, this dissertation proposes EFL teachers to use the EFL through Play and Art” philosophy as a valid alternative teaching strategy instead of regular textbook activities.